Association Study Between Thermal Front Phenomena and Bali Sardinella Fishing Areas in Bali Strait - Argo Galih Suhadha; Andi Ibrahim (Faculty of Geography, Universitas Gadjah Mada, 2020)
Thermal front has been widely used as a parameter for determining ﬁshing zones. Tis study aimed to determine the thermal front distribution and to analyze its association with the Bali Sardinella ﬁshing zones in the Bali Strait. Termal front generated using sea surface temperature (SST) from Aqua MODIS imagery. Meanwhile, the ﬁshing point data of Bali Sardinella were collected to validate our analysis results. Te data were analyzed into Spatio-temporal information. Te main facts that stand out are that the thermal front was predominantly found in the peak of ﬁrst (April) and second (September) transitional season, which was the peak season for the thermal front to occur in a year. Te least of the thermal front occurred in the South-west monsoon. Te linear relationship was found when the peak of thermal front occurrence compared to the number of catch yields. Based on matching distance analysis, the maximum distance used (twenty kilometres buﬀer) show 36 matching points from 101 data compared or at range 35.6%. In conclusion, there is a linear relationship between the thermal front parameter and catch yield. It is still used to predict the ﬁshing zone, even though the correlation is not signiﬁcantly found.